THE RECONSTRUCTION OF FUNCTIONS USING DIDACTIC TRANSPOSITION: A FOCUS ON THE TEXTBOOKS FOLLOWING THE MALAYSIAN AND INDONESIAN MATHEMATICS CURRICULA - Nadya Syifa Utami; Sufyani Prabawanto; Phoong Seuk Yen; Arrold Rynix Anak Rambee (Malaysian Journal of Learning and Instruction, 2025)
Purpose – This study is aimed at exploring how the topic of functions was organised into knowledge to be delivered in textbooks based on the Malaysian and Indonesian mathematics curriculum, and how the topic reconstruction in both countries differed.